ANALISIS PERHITUNGAN EFEKTIVITAS PADA MESIN RYOBY UNTUK MENINGKATKAN PRODUKTIVITAS DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENES (OEE) DAN SIX BIG LOSSES DI CV. KYTA JAYA MANDIRI - Affan Anshori (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
CV. Kyta Jaya Mandiri used for the offset priting process has not been fully effective. This is indicated by a decrease in engine speed and produce print that is not in accordance with established standards. This study aims to measure and determine the effectiveness of ryobi machines using the overall equipment effectiveness (oee) method. Overall equipment effectiveness (oee) is a tool to measure the effectiveness of machine tools based on three categories, namely availability, performance effeciency, quality. This study also uses fishbone diagrams, to identify six big losses. The results of the study the overall equiment effectiveness (oee) value of 63.42% which means that it is still below the jipm standard that is oee> 85%. The most dominant factor affecting the effectiveness of the ryobi engine is the reduce speed losses value of 35.30% of alltime losses. What was done to anticipate the low overall equiment effectiveness (oee) value on the ryobi machine is by holding an autonomous maintenance given to the operator, doing regular preventive maintenance to maintain engine performance. Carry out training for operators and maintenance technicians as well as supervise operators regarding workplace cleanliness.Â keywords: overall equipment effectiveness, six big losses and tpm